Statistical foundation of data science - Fan, Jianqing; Li, Runze; Zhang, Cun-Hui; Zou, Hui (Boca Raton: CRC Press, 2020)
"Statistical Foundations of Data Science gives a thorough introduction to commonly used statistical models, contemporary statistical machine learning techniques and algorithms, along with their mathematical insights and statistical theories. It aims to serve as a graduate-level textbook and a research monograph on high-dimensional statistics, sparsity and covariance learning, machine learning, and statistical inference. It includes ample exercises that involve both theoretical studies as well as empirical applications"--